Characterization of cylindrical nano-domains in thin films of polystyrene-poly(methyl methacrylate) diblock copolymer studied via atomic force microscopy - Maire, Helene C. (Kansas State University, 2008)
We have investigated the orientation of cylindrical domains in thin films of a polystyrene–poly(methylmethacrylate) diblock copolymer (PS-b-PMMA) on planar substrates having different surface roughnesses and hydrophilicities. The research in this dissertation covers the substrate surface modifications, the enhancement of the diblock copolymer film coating, and the refinement of the treatments leading to nanoporous material. Treatment of the substrate with organic mercaptans forming self-assembled-monolayer (SAM), leading to various hydrophilicities of the surfaces, was inconclusive as far as orienting the PMMA domains in the PS matrix due to thermal instability of some thiols. This directed us to a different approach involving substrate roughness. PS-b-PMMA films of 20~200 nm thick were prepared via spin-coating on silicon, gold or indium tin oxide (ITO) substrates, and annealed in vacuum at 170 °C for 60 hours to induce the formation of cylindrical PMMA domains. Atomic force microscopy (AFM) images indicated the domain orientation at the free surface. In PS-b-PMMA films much thicker than the domain periodicity (L0), the domains were oriented perpendicularly to the free surface regardless of underlying substrates, reflecting the balanced interactions of PS and PMMA blocks at the polymer–vacuum interface. In films having thickness similar to L0, vertically oriented domains were observed on the Au and ITO surfaces that are covered with nanoscale grains, whereas horizontal domains were observed on the smooth Si substrates. In particular, the cylindrical PMMA domains were efficiently perpendicularly aligned when the grain size nearly was equal to L0. The perpendicular domain alignment induced by the substrate roughness was corroborated using cyclic voltammetry (CV) for gold substrates coated with PS-b-PMMA films whose PMMA domains were removed by UV and subsequent acetic acid treatments. The CV data also suggested that the PMMA domains were successfully removed, leaving a nanoporous stable PS matrix on the substrate.
Keywords: diblock copolymer; cylindrical nano-domains; thin films of PS-b-PMMA; Chemistry, Analytical (0486)